The coal measures and coal veins of Kansas a review of the geology of Kansas coals - Harvey, William Lee (My University, 1902)
Introduction: In the eastern part of Kansas covering about one fourth of its area or 20,000 square miles, lays the Kansas Coal Measures. The western line of the coal deposits forms an irregular line crossing the state from eastern Brown County to western Chautauqua County. In addition we have the cretaceous coal area in the north-central part of the state. For the counties that produce coal the reader is referred to plate VII. The Kansas Coal Measures compose a mass of alternating beds of limestones, sandstones and shales approximately 3000 feet thick. There are hardly enough distinguishing characteristics in the various beds of limestone to warrant a different name; however the lower the limestone the finer the texture and the more highly crystalline. Also the upper layers are lighter in color, sometimes almost pure white.
Citation: Harvey, William Lee. The coal measures and coal veins of Kansas a review of the geology of Kansas coals. Senior thesis, Kansas State Agricultural College, 1902.
Morse Department of Special Collections
Keywords: Kansas Coal Measures; Coal; Kansas; Geology; Theses; Manuscripts (documents)